2000
DOI: 10.1177/031289620002500204
|View full text |Cite
|
Sign up to set email alerts
|

Market Orientation and Company Profitability: Further Evidence Incorporating Longitudinal Data

Abstract: This study examines the association between market orientation and company profitability. It incorporates two methodological approaches that have generally not been used in previous research. First, it uses lagged company and environmental control variables in the data analysis, to better discern their effects on profitability and, hence, clarify any relationship between market orientation and perfor Mance. Second, it analyses the individual components of market orientation and their relationships with busines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
168
0
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(184 citation statements)
references
References 63 publications
(95 reference statements)
7
168
0
7
Order By: Relevance
“…This was found to be consistent with the findings of the empirical study conducted by Boohene et tal (2012), who established a positive relationship between market orientation and its components and financial performance of small businesses in the Takoradi metropolis. It is also in conformity with the findings of Dawes (2000), who asserted that as a result of unique characteristics of each of the elements of MO, each MO component is not necessarily equally and strongly associated with profitability.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This was found to be consistent with the findings of the empirical study conducted by Boohene et tal (2012), who established a positive relationship between market orientation and its components and financial performance of small businesses in the Takoradi metropolis. It is also in conformity with the findings of Dawes (2000), who asserted that as a result of unique characteristics of each of the elements of MO, each MO component is not necessarily equally and strongly associated with profitability.…”
Section: Resultssupporting
confidence: 89%
“…This may be as a result of unique characteristics of each of the elements of market orientation. Thus, Dawes (2000) emphasize that each MO component is not necessarily equally and strongly associated with profitability. Thus, the following hypothesis was, therefore, developed to be tested:…”
Section: Market Orientation and Firm Performancementioning
confidence: 99%
“…In this condition, common methods variance may strengthen the correlation between market orientation and performance when research uses a subjective measure (Doty & Glick, 1998). Dawes (1999) also presents the danger of obtaining a false positive result (i.e. Type I Error) when using subjective rather than objective measures of business performance.…”
Section: Antecedents Of Market Orientationmentioning
confidence: 99%
“…In a study of market orientation and company profitability, further evidence incorporating longitudinal data, Dawes (2000) found that the components of a market orientation, competitor orientation emerged the strongest association with performance. Likewise, study by Ellis (2006) also supports the relationship between market orientation and firm performance.…”
Section: Market Orientation and Organizational Performance Relationshipmentioning
confidence: 99%